763 ACTIVATION OF SIRT1 ATTENUATES VASCULAR DYSFUNCTION AND THROMBOSIS IN MTHFR DEFICIENCY. (15th December 2022) - Carrizzo, Albino; Iside, Concetta; Nebbioso, Angela; Carafa, Vincenzo; Damato, Antonio; Ciccarelli, Michele; Venturini, Eleonora; Di Pietro, Paola; Trimarco, Bruno; Selleri, Carmine; Altucci, Lucia; Vecchione, Carmine
Abstract: Beyond well-assessed risk factors, cardiovascular events could be also associated with the presence of epigenetic and genetic alterations, such as the methylenetetrahydrofolate-reductase ( MTHFR ) C677T polymorphism. This gene variant is related to increased circulating levels of homocysteine (Hcy) and cardiovascular risk. However, heterozygous carriers have an augmented risk of cardiovascular accidents independently from normal Hcy levels, suggesting the presence of additional deregulated processes in MTHFR C677T carriers. Here we hypothesize that targeting Sirtuin 1 (SIRT1) could be an alternative mechanism to control the cardiovascular risk associated to MTHFR deficiency condition. Flow Mediated Dilatation (FMD) and light transmission aggregometry assay were performed in subjects carrying MTHFR C677T allele after administration of resveratrol, the most powerful natural clinical usable compound that owns SIRT1 activating properties. MTHFR C677T carriers with normal Hcy levels revealed endothelial dysfunction and enhanced platelet aggregation associated with SIRT1 downregulation. SIRT1 activity stimulation by resveratrol intake was able to override these abnormalities without affecting Hcy levels. Impaired endothelial function, bleeding time, and wire-induced thrombus formation were rescued in a heterozygous Mthfr -deficient ( Mthfr +/- ) mouse model after resveratrol treatment. Using a cell-based high-throughput multiplexed screening (HTS) assay, a novel selective synthetic SIRT1 activator, namely ISIDE11, was identified. Ex vivo and in vivo treatment of Mthfr +/- mice with ISIDE11 rescues endothelial vasorelaxation and reduces wire-induced thrombus formation, effects that were abolished by SIRT1 inhibitor. Moreover, platelets from MTHFR C677T allele carriers treated with ISIDE11 showed normalization of their typical hyper-reactivity. These results candidate SIRT1 activation as a new therapeutic strategy to contain cardio and cerebrovascular events in MTHFR carriers.